The Visual Imagery through Elements of Rhetoric in Kun Fayakun Novel by Andi Bombang - Sari, Ratna Intan; Supriyanto, RM. Teguh; Doyin, Mukh. (Universitas Negeri Semarang, 2023)
This article focuses on the study of the use of language forms in the realm of visual imagery that are built from rhetorical elements to Andi Bombang's Kun Fayakun novel using a qualitative approach through stylistic theory. The purpose of this study is to explain the visual imagery built from the rhetorical elements in Andi Bombang's Kun Fayakun novel. The rhetorical elements that are the focus of discussion in this study are figurative language or comparative types of figurative language, including metaphors, personifications, and similes. The data used are all language signs in the novel Kun Fayakun by Andi Bombang which are also useful as data sources. This study uses a semiotic method with a first-level reading technique, heuristics, for data collection and a second-level reading technique, hermeneutics, for data analysis. The results of this study show an explanation of the use of language forms in the realm of visual imagery that are built from rhetorical elements in Andi Bombang's Kun Fayakun novel. The use of visual imagery through rhetorical elements in the novel is used as an embodiment of a more real picture and an emphasis on meaning related to story events so that the reader can create concrete images.